Mapping of Lviv in the soviet period - Сосса, Р. І.; Sossa, R. (Видавництво Національного університету “Львівська політехніка”, 2020)
Плани Львова досліджено з позицій їх цільового призначення, умов створення, змістовного наповнення, відповідності нормативним документам. Визначено особливості створення та змісту основних типів планів міста для військових потреб, для потреб господарського розвитку міста, для туристів і мешканців міста. Картографування Львова визначено розвитком суспільних процесів у державі та відповідно домінуючими тенденціями розвитку картографування в СРСР. Характерними ознаками цього періоду були утаємниченість картографічної інформації та режимні обмеження на створення й використання різноманітних карт. Військові топографічні плани масштабу 1:10 000 та великомасштабні (1:5 000, 1:2 000) плани міста для господарських цілей видавали тільки з грифом “таємно”. На початок 1980-х років місто було забезпечено топографічними багатоаркушевими планами у масштабах 1:2 000 і 1:5 000. Дуже спрощені схеми Львова для гостей і жителів міста до початку 1970-х років видавали книжкові видавництва. З 1974 р. картографічні підприємства ГУГК монопольно випускають туристичні схеми міста із спотвореною та значно розвантаженою основою. Лише наприкінці 1980-х років із зменшенням режимних обмежень на відображення елементів географічної основи картографічна якість туристичних планів Львова поліпшується.

Objective of our research is to identify the specific nature and common trends of Lviv mapping for government and social needs in the Soviet period. Methodology. The contemporary understanding of a map to be an important document that contains geospatial information and of mapping to be an important method of documenting events and phenomena are the theoretical and methodological basis for the research. Studying Lviv mapping over a certain period of time covers studying the history of ideas and methods of mapping, map production and maps themselves. The research has considered the social and political reality of the USSR and the effect it had on the mapping process. Results. Lviv city maps have been researched from the perspective of their intended use, map-making conditions, information, and regulatory compliance. Specific nature of map-making and information of the city maps for military needs, for the city business development needs, for the needs of the city guests and residents has been outlined. Lviv mapping was predetermined by the social processes within the state and by the accordingly prevailing trends of mapping development in the USSR. Secrecy of mapping information and security restrictions of making and using various maps was typical feature of that period. 1:10 000 scale military topographic maps and large 1:5 000, 1:2 000 scale city maps for business needs were only published “secret”-marked. In early 1980s, the city was provisioned with 1:2 000 and 1:5 000 scale multi-sheet topographic maps. Until the beginning of 1970, light-version Lviv city layouts for guests and residents were published by book publishers. Starting 1974, cartography companies of the Central Authority for Geodesy and Cartography (GUGK) began exclusively publishing tourist-oriented Lviv layouts with distorted and very lightened basis. Only in late 1980s, as the security restrictions for mapping the geographic basis got mitigated, the quality of Lviv maps for tourists started getting better. Scientific novelty of the research is that it is the first time when mapping of the Soviet period Lviv has been studied chronologically, from a different perspective. Practical relevance of the research results is various Lviv maps and layouts found, and the prerequisites, methods and principles of their compilation.
Картографування Львова в радянський період
Keywords: Львів; план міста; топографічний план; схематичний план; туристичний план; таємність картографічних робіт; цензура; спотворення географічної основи; Lviv city topographic maps; Lviv city layouts; Lviv city maps for tourists; mapping secrecy; plan’s quality; distorted geographic basis; 528